Effects of six-year biochar amendment on soil aggregation, crop growth, and nitrogen and phosphorus use efficiencies in a rice-wheat rotation. (1st January 2020) - Zhang, Qianqian; Song, Yanfeng; Wu, Zhen; Yan, Xiaoyuan; Gunina, Anna; Kuzyakov, Yakov; Xiong, Zhengqin
Abstract: The effective use of biochar as biomass recycling in agriculture to improve both crop production and environmental performance requires an understanding of its effects on soil nutrients, i.e., nitrogen (N) and phosphorus (P) and soil structure and soil carbon stocks. Thus, crop yield, soil aggregate stability and N and P use efficiencies (NUE and PUE, respectively) were investigated in a rice-wheat rotation field experiment 6 years after biochar amendment (20 and 40 t ha −1 ). Biochar application increased crop (rice and wheat) root (by 3–19%), straw (by 10–19%) and grain (by 10–16%) biomasses, as well as grain NUE (by 20–53%) and PUE (by 38–230%) compared with N fertilization only, whereas decreases in the N stocks in the root (2–5%), straw (13–17%) and grain (0–2%) occurred after biochar addition in the rice growth stage. No differences were observed between 20 and 40 t ha −1 biochar with respect to root, straw and grain biomasses as well as NUE and PUE. Biochar improved soil organic carbon (by 26–53%), total N (by 14–16%) and P (by 6–19%) compared to N fertilization only and positively affected the 250–2000 μm aggregate class (by 87–93%) and aggregate stability (by 43–48%). Based on structural equation modeling (SEM), this additional carbon affected aggregate stability by improving the aggregate structure, whereas P affected aggregate stability directly in biochar-fertilized soils. Improvement of soil carbon stocks and nutrient pools (i.e., N, P), promoted root growth, uptake of N and P fertilizers and crop production. Thus, biochar application is an effective strategy to increase crop yield, even in the long-term, and is connected not only with the improvement of soil structure and carbon stocks but also with increases in nutrient use efficiency. Graphical abstract: Image 1